Duration of spermatogenesis and daily sperm production in the rodent Proechimys guyannensis. Issue 5 (16th June 2016) - Lara, Nathália L.M.; Santos, Ivan C.; Costa, Guilherme M.J.; Cordeiro-Junior, Dirceu A.; Almeida, Antônio C. G.; Madureira, Ana P.; Zanini, Marcos S.; França, Luiz R.
Summary: The spiny rat ( Proechimys guyannensis ) is a neotropical rodent that is used in biomedical research, particularly research related to chronic resistance to epilepsy and infectious diseases. To our knowledge, there are few reports concerning the reproductive biology of this species. Therefore, besides providing basic biometric and morphometric data, in the present study we investigated testis function and spermatogenesis in adult spiny rats. The mean testis weight and gonadosomatic index obtained were 1.63 ± 0.2 g and 1.15 ± 0.1% respectively. Based on the development of the acrosomic system, 12 stages of the seminiferous epithelium cycle were characterized. Stages VI and VII presented the highest frequencies (~17–19%), whilst stages II to V showed the lowest frequencies (~2–4%). The most advanced germ cell types labelled at 1 h or 20 days after BrdU injections were respectively preleptotene/leptotene spermatocytes at stage VII and elongated spermatids at stage III. The mean duration of one cycle was 7.5 ± 0.01 days and the entire spermatogenic process lasted 33.7 ± 0.06 days (~4.5 cycles). The seminiferous tubules (ST) occupied ~96 ± 1% of the testis parenchyma, whereas Leydig cells comprised only 1.5 ± 0.4%. The number of Sertoli cells (SC) per testis gram and the SC efficiency (spermatids/SC) were respectively 78 × 10 6 ± 11 × 10 6 and 7.9 ± 1. The daily sperm production per testis gram (spermatogenic efficiency; daily sperm production (DSP)/g/testis) was 78 × 10 6 ± 8 × 10 6 . To our knowledge, this spermatogenic efficiency is among the highest found for mammals investigated to date and is probably related to the very short duration of spermatogenesis and the very high ST percentage and SC number obtained for this species.